2013
DOI: 10.1163/1568539x-00003054
|View full text |Cite
|
Sign up to set email alerts
|

Sources of background noise and their influence on vertebrate acoustic communication

Abstract: Many animals rely on long-range communication for species recognition, mate selection and territorial defense, but background noise from the environment can constrain their communication. Background noise from both biotic and abiotic sources is ubiquitous. In general, acoustic noise from abiotic sources, including anthropogenic noise, has energy mostly below 1 kHz. Arthropods tend to produce sounds in the 4-10 kHz range, while birds, amphibians and mammals generally have vocalizations with frequencies between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 88 publications
3
51
0
1
Order By: Relevance
“…This omission from the literature is surprising given that many animals are often exposed to sudden changes in noise levels. In undeveloped natural habitats, falling branches, gusts of wind or the calls of conspecifics and heterospecifics are potential sources of intermittent high-amplitude noise bursts (Luther and Gentry, 2013). In urban areas, peaks in traffic during the morning and evening rush hours contribute to a daily fluctuation in noise levels, while short bursts of often very loud noise from sources such as car alarms, car horns, construction work or passing vehicles are common throughout the day (Warren et al, 2006;Luther and Gentry, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This omission from the literature is surprising given that many animals are often exposed to sudden changes in noise levels. In undeveloped natural habitats, falling branches, gusts of wind or the calls of conspecifics and heterospecifics are potential sources of intermittent high-amplitude noise bursts (Luther and Gentry, 2013). In urban areas, peaks in traffic during the morning and evening rush hours contribute to a daily fluctuation in noise levels, while short bursts of often very loud noise from sources such as car alarms, car horns, construction work or passing vehicles are common throughout the day (Warren et al, 2006;Luther and Gentry, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that animals can adjust aspects of acoustic communication (e.g. call frequency, amplitude and duration) to compensate for background noise [8,9]. Examples of adaptations for visual signals are relatively rare, but some bird species have been shown to orient or selectively display in sunlight to increase the conspicuousness of iridescent or short-wavelength-rich plumage [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic communication is a critical element involved in many different aspects of animal life, but especially so in avian systems, where it plays a key role in competition, mate attraction and reproduction (Collins, 2004). Because vocal communication is so important to avian fitness, human interference on signal transmission and perception is of paramount concern (Rabin & Greene, 2002;Patricelli & Blickley, 2006;Slabbekoom & den Boer-Visser, 2006;Warren et al, 2006;Luther & Gentry, 2013).…”
Section: Urbanizationmentioning
confidence: 99%